A review of spatial reasoning and interaction for real-world robotics. (4th March 2017) - Landsiedel, C.; Rieser, V.; Walter, M.; Wollherr, D.
Abstract : Truly universal helper robots capable of coping with unknown, unstructured environments must be capable of spatial reasoning, i.e. establishing geometric relations between objects and locations, expressing those in terms understandable by humans. It is therefore desirable that spatial and semantic environment representations are tightly interlinked. 3D robotic mapping and the generation of consistent metric representations of space are highly useful for navigation and exploration, but they do not capture symbol-level information about the environment. This is, however, essential for reasoning, and enables interaction via natural language, which is arguably the most common and natural communication channel used and understood by humans. This article presents a review of research in three major fields relevant for this discussion of spatial reasoning and interaction. Firstly, dialogue systems are an integral part of modern approaches to situated human–robot interaction. Secondly, interactive robots must be equipped with environment representations and reasoning methods that are suitable for both navigation and task fulfillment, as well as for interaction with human partners. Thirdly, at the interface between these domains are systems that ground language in systemic environment representation and which allow the integration of information from natural language descriptions into robotic maps. For each of these areas, important approaches are outlined and relations between the fields are highlighted, and challenging applications as well as open problems are discussed.